How Teachers' Literacy Practices Shape Early Childhood Literacy Development: A Structural Mediation Model from Kindergartens in Nganjuk Regency - Destita Shari; Sri Katoningsih; Winnuly Winnuly; Laras Nur Indah Prawesti (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
Early childhood literacy development establishes a critical foundation for subsequent academic achievement; however, the mechanisms through which teachers’ instructional practices influence children’s literacy outcomes remain underexplored within Indonesian educational contexts. This study investigates structural pathways among teachers’ literacy practices, classroom literacy environment, children’s engagement in literacy activities, and early literacy development in 255 kindergarten children aged 4–6 years across Nganjuk Regency, East Java, Indonesia. Employing a quantitative correlational design using Structural Equation Modeling, with data collected following an eight-week literacy instructional program, data were collected using a structured instrument measuring four latent constructs via ten indicators each on a five-point Likert scale. Structural Equation Modeling with AMOS 26 and bootstrap analysis (5,000 resamples) examined direct and indirect effects. Results demonstrate that teachers’ literacy practices significantly predict early childhood literacy development both directly (β = .21, p < .01) and indirectly through sequential mediation by classroom literacy environment and children’s engagement (β = .10, p < .01). The strongest pathway emerged between teachers’.